Glycosyl‐Substituted Dicarboxylates as Detergents for the Extraction, Overstabilization, and Crystallization of Membrane Proteins. Issue 11 (13th February 2018) - Nguyen, Kim‐Anh; Peuchmaur, Marine; Magnard, Sandrine; Haudecoeur, Romain; Boyère, Cédric; Mounien, Saravanan; Benammar, Ikram; Zampieri, Veronica; Igonet, Sébastien; Chaptal, Vincent; Jawhari, Anass; Boumendjel, Ahcène; et al.
Abstract: To tackle the problems associated with membrane protein (MP) instability in detergent solutions, we designed a series of glycosyl‐substituted dicarboxylate detergents (DCODs) in which we optimized the polar head to clamp the membrane domain by including, on one side, two carboxyl groups that form salt bridges with basic residues abundant at the membrane–cytoplasm interface of MPs and, on the other side, a sugar to form hydrogen bonds. Upon extraction, the DCODs 8 b, 8 c, and 9 b preserved the ATPase function of BmrA, an ATP‐binding cassette pump, much more efficiently than reference or recently designed detergents. The DCODs 8 a, 8 b, 8 f, 9 a, and 9 b induced thermal shifts of 20 to 29 °C for BmrA and of 13 to 21 °C for the native version of the G‐protein‐coupled adenosine receptor A2A R. Compounds 8 f and 8 g improved the diffraction resolution of BmrA crystals from 6 to 4 Å. DCODs are therefore considered to be promising and powerful tools for the structural biology of MPs. Abstract : Detergents used for extracting membrane proteins (MPs) in aqueous solutions tend to destabilize them because of their high exchangeability. Glycosyl‐substituted dicarboxylate detergents clamp the membrane domain and form salt bridges with basic residues of the MPs. They preserve the ATPase function of BmrA upon extraction, and improve its stability and crystallization.